2016
DOI: 10.1107/s1600576716012115
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized in-plane ordering of nanostructures at epitaxial ferroelectric–ferromagnetic interfaces

Abstract: The formation of self‐assembled structures is of great interest in the field of ferroelectric (FE)–ferromagnetic (FM) oxide interfaces with novel functionalities driven by the combination of strain relaxation and diffusion/segregation processes occurring during epitaxial growth of Mn‐based heterostructures. In epitaxial bilayers and multilayers of La0.67Sr0.33MnO3 (LSMO)/BaTiO3 (BTO) on (001) SrTiO3, using the grazing‐incidence small‐angle X‐ray scattering technique, self‐assembled in‐plane structural ordering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…One may note that a full strain relaxation typically occurs above a thickness of 100 nm. Initial sample characterizations 11 were done using X-ray reflectivity (XRR) and X-ray diffraction (XRD) and has been shown in the supplementary section.…”
Section: Resultsmentioning
confidence: 99%
“…One may note that a full strain relaxation typically occurs above a thickness of 100 nm. Initial sample characterizations 11 were done using X-ray reflectivity (XRR) and X-ray diffraction (XRD) and has been shown in the supplementary section.…”
Section: Resultsmentioning
confidence: 99%
“…The “remote” heteroepitaxy, as an alternative approach to the direct heteroepitaxy, has been recently reported, where a graphene interlayer partially screens the substrate electrostatic potential, reduces the nucleation rate, and simultaneously promotes the growth of the epilayer. It is demonstrated that the amount of energetically favorable dislocations for relaxing the lattice strain, which primarily results from a lattice mismatch between the overgrown layer and the host substrate, can be largely reduced thanks to two-dimensional (2D) materials that alleviate the interaction when the graphene-coated substrate was used for epitaxy. , In this regard, epitaxial III–V materials with low-density defects have been successfully grown on top of mono- or bilayer graphene-coated substrates, followed by exfoliation and transfer onto the target substrate to produce high-quality devices. , In such cases, the self-organized in-plane ordering of nanostructures has been found to be important for various functional heterostructures . On the other hand, complex-oxide materials showing extensive functionalities including ferromagnetism, ferroelectricity, and piezoelectricity have also been explored to realize epitaxial growth on graphene-buffered substrates. , For example, Kum et al demonstrated high-quality single-crystalline BaTiO 3 (BTO) and SrTiO 3 (STO) epilayers grown on graphene-coated STO substrates .…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 In such cases, the self-organized in-plane ordering of nanostructures has been found to be important for various functional heterostructures. 26 On the other hand, complex-oxide materials showing extensive functionalities including ferromagnetism, ferroelectricity, and piezoelectricity have also been explored to realize epitaxial growth on graphene-buffered substrates. 22 , 27 For example, Kum et al demonstrated high-quality single-crystalline BaTiO 3 (BTO) and SrTiO 3 (STO) epilayers grown on graphene-coated STO substrates.…”
Section: Introductionmentioning
confidence: 99%